Convergence of IRBIT, phosphatidylinositol (4,5) bisphosphate, and WNK/SPAK kinases in regulation of the Na(+)-HCO(3)(−) cotransporters family - Hong, Jeong Hee (National Academy of Sciences, 2013)
Fluid and HCO(3)(−) secretion is a vital function of secretory epithelia, involving basolateral HCO(3)(−) entry through the Na(+)-HCO(3)(−) cotransporter (NBC) NBCe1-B, and luminal HCO(3)(−) exit mediated by cystic fibrosis transmembrane conductance regulator (CFTR) and solute carrier family 26 (SLC26) Cl(−)/HCO(3)(−) exchangers. HCO(3)(−) secretion is highly regulated, with the WNK/SPAK kinase pathway setting the resting state and the IRBIT/PP1 pathway setting the stimulated state. However, we know little about the relationships between the WNK/SPAK and IRBIT/PP1 sites in the regulation of the transporters. The first 85 N-terminal amino acids of NBCe1-B function as an autoinhibitory domain. Here we have identified a positively charged module within NBCe1-B(37-65) that is conserved in NBCn1-A and all 20 members of the NBC superfamily except NBCe1-A. This module is required for the interaction and activation of NBCe1-B and NBCn1-A by IRBIT and their regulation by phosphatidylinositol 4,5-bisphosphate (PIP(2)). Activation of the transporters by IRBIT and PIP(2) is nonadditive but complementary. Phosphorylation of Ser65 mediates regulation of NBCe1-B by SPAK, and phosphorylation of Thr49 is required for regulation by IRBIT and SPAK. Sequence searches using the NBCe1-B regulatory module as a template identified a homologous sequence in the CFTR R domain and Slc26a6 sulfat transporter and antisigma factor antagonist (STAS) domain. Accordingly, the R and STAS domains bind IRBIT, and the R domain is required for activation of CFTR by IRBIT. These findings reveal convergence of regulatory modalities in a conserved domain of the NBC that may be present in other HCO(3)(−) transporters and thus in the regulation of epithelial fluid and HCO(3)(−) secretion.